1993
DOI: 10.1002/jez.1402650204
|View full text |Cite
|
Sign up to set email alerts
|

Brain evolution in decapod crustacea

Abstract: A survey of the morphology of the brains (cerebral ganglia) of 13 species of decapods shows that all have common areas of neuropil that are developed to differing degrees in the different groups. The neuropils of the paired accessory lobes, however, appear to have evolved de novo in the Reptantia. Phylogenetic relationships within the Reptantia suggest that the accessory lobes were initially large but became reduced in size during the evolution of the brachyurans and anomalans. The cerebral ganglia of many art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
147
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(153 citation statements)
references
References 14 publications
5
147
1
Order By: Relevance
“…The present examinations show that the red shrimp brain conforms to the typical decapod brain as indicated also by the presence of the 'olfactory lobe cell masses' (OLCMs) in the deuterocerebrum (SANDEMAN et al, 1993).…”
Section: Resultssupporting
confidence: 69%
“…The present examinations show that the red shrimp brain conforms to the typical decapod brain as indicated also by the presence of the 'olfactory lobe cell masses' (OLCMs) in the deuterocerebrum (SANDEMAN et al, 1993).…”
Section: Resultssupporting
confidence: 69%
“…2a). The neuronal somata in Malacostraca are also clustered in characteristic groups (18,19). We propose that the remipede clusters A͞B and G correspond to the malacostracan clusters 6͞7 and 12͞13, respectively.…”
Section: Resultsmentioning
confidence: 85%
“…3), a relatively diffuse block of neuropil crossing the midline of the brain, which contains a transverse commissural fiber bundle linking the deutocerebral hemispheres. Furthermore, the paired lateral antenna 1 neuropils [LAN in accordance with the malacostracan nomenclature (18,19)] are part of the deutocerebrum and receive a distinct input from the nerves of the first antennae (A1Nv). They are associated with cell clusters C and D (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…By increasing the span of the sensor, the copepod can compare a spatially wider gradient, and also possibly a weaker one. Sandeman et al (1993) have suggested that long chemosensory or mechanosensory appendages (and corresponding increases in the size of particular regions in the brain), may be associated with processing odour (and/or mechanosensory) information in spatially complex habitats. Hence, sensors with large spans may permit increased spatial resolution of chemical signals, as has been postulated for the forked tongue of snakes (Schwenk 1994).…”
Section: (Iii) Edge Detectionmentioning
confidence: 99%